ADVANTAGES AND CHALLENGES OF TABLET PC’S USAGE - ČIČEVIĆ, Svetlana; MITROVIĆ, Slobodan; NEŠIĆ, Milkica (Yugoslav Journal of Operations Research, 2017)
In this study we were interested in evaluating tablet PC device performances, as well as how the respondents perceived its usability. Usability of this kind of device is furthermore investigated in comparison to the other similar mobile devices. The Technique for Order Preferences by Similarity to an Ideal Solution (TOPSIS) is specifically implemented and its outcomes are compared with the calculated System Usability Scale (SUS) scores. One of the TOPSIS method advantages is its ability to identify the best alternative quickly and precisely, which is also one of the most important features of SUS scale.